Association of oral status with frailty among older adults in nursing homes: a cross-sectional study - Siyue Liu; Yicong Guo; Zhao Hu; Feixiang Zhou; Shaojie Li; Huilan Xu (BMC Oral Health, 2023)
Abstract Background The oral status of an individual is a vital aspect of their overall health. However, older adults in nursing homes have a higher prevalence of frailty and poor oral health, particularly in the context of global aging. The objective of this study is to explore the association between oral status and frailty among older adults residing in nursing homes. Methods The study involved 1280 individuals aged 60 and above from nursing homes in Hunan province, China. A simple frailty questionnaire (FRAIL scale) was used to evaluate physical frailty, while the Oral Health Assessment Tool was used to assess oral status. The frequency of tooth brushing was classified as never, once a day, and twice or more a day. The traditional multinomial logistic regression model was used to analyze the association between oral status and frailty. Adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated while controlling for other confounding factors. Results The study found that the prevalence of frailty among older adults living in nursing homes was 53.6%, while the prevalence of pre-frailty was 36.3%. After controlling for all potential confounding factors, mouth changes requiring monitoring (OR = 2.10, 95% CI = 1.34–3.31, P = 0.001) and unhealthy mouth (OR = 2.55, 95% CI = 1.61–4.06, P < 0.001) were significantly associated with increased odds of frailty among older adults in nursing homes. Similarly, both mouth changes requiring monitoring (OR = 1.91, 95% CI = 1.20–3.06, P = 0.007) and unhealthy mouth (OR = 2.24, 95% CI = 1.39–3.63, P = 0.001) were significantly associated with a higher prevalence of pre-frailty. Moreover, brushing teeth twice or more times a day was found to be significantly associated with a lower prevalence of both pre-frailty (OR = 0.55, 95% CI = 0.34–0.88, P = 0.013) and frailty (OR = 0.50, 95% CI = 0.32–0.78, P = 0.002). Conversely, never brushing teeth was significantly associated with higher odds of pre-frailty (OR = 1.82, 95% CI = 1.09–3.05, P = 0.022) and frailty (OR = 1.74, 95% CI = 1.06–2.88, P = 0.030). Conclusions Mouth changes that require monitoring and unhealthy mouth increase the likelihood of frailty among older adults in nursing homes. On the other hand, those who brush their teeth frequently have a lower prevalence of frailty. However, further research is needed to determine whether improving the oral status of older adults can change their level of frailty.